Implkasi Kegiatan Pembelajaran Menggunakan Problem Solving Lab & Higher Order Thinking Lab pada Kegiatan Praktikum - Singgih, Singgih Panita Budiman; Budiman, Singgih Panita Budiman; Malik, Adam (Physics and Science Education Journal (PSEJ), 2025)
This study aims to determine the implications of laboratory activities using problem solving laboratory and higher order thinking laboratory learning models. This type of research uses a type of literature study research. The literature study procedure includes several steps; determine the goals and objects of study, collect sources, analyze information, repeat and correct, and compile research results. The target of the research carried out in this research this is for teachers, students & students who carry out practicum activities, especially in the Department of Mathematics / Physics. Experimental activities in the laboratory are able to assist students in understanding science subjects effectively; Therefore, it is an integral part of science education. The physics laboratory is an important part and is implemented as an independent course. The implications for the application of the problem solving laboratory 7 &higher order thinking laboratory model can improve The intellectual process skillfully, conceptualizes, implements, analyzes, synthesizes information resulting from experience, observation, reflection, reasoning, or communication as a rubric of belief and action.